1 3/4 + 2 1/3

= 1 9/12 + 2 4/12 (we have renamed the fractions so we can add them)

= (1+2) + (9/12 + 4/12)

= 3 + 13/12 (here is our sum)

= 3 + (12 + 1)/12 (now, we are renaming the improper fraction)

= 3 + 12/12 + 1/12 (into an integer part and a fraction part)

= 3 + 1 + 1/12 (here we show the integer and fraction)

= 4 + 1/12 (the integers are added to complete the renaming of the integer part)

= 4 1/12 (here we rename the sum as a mixed number)

= 1 9/12 + 2 4/12 (we have renamed the fractions so we can add them)

= (1+2) + (9/12 + 4/12)

= 3 + 13/12 (here is our sum)

= 3 + (12 + 1)/12 (now, we are renaming the improper fraction)

= 3 + 12/12 + 1/12 (into an integer part and a fraction part)

= 3 + 1 + 1/12 (here we show the integer and fraction)

= 4 + 1/12 (the integers are added to complete the renaming of the integer part)

= 4 1/12 (here we rename the sum as a mixed number)